MODEL KEPEMIMPINAN KEPALA MADRASAH DALAM PENINGKATAN KOMPETENSI PEDAGOGIK GURU MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM - Pandri (UNISAN JURNAL, 2023)
This study aims to find out about the leadership model of the madrasa head in increasing the pedagogic competence of teachers in Islamic cultural history subjects. This research is classified as a qualitative research because the research was conducted in natural conditions. The leadership model of the Principal of MA Islamiyah Simpang, Oku Selatan in Improving the Pedagogic Competence of SKI Teachers that is applied is a contingency or situational leadership model. The leadership strategy of the Head of MA Islamiyah Simpang, Oku Selatan in Improving the Pedagogic Competence of SKI Teachers is to use a participatory strategy.